Green Synthesis of Reduced Graphene Oxide Using Ascorbic Acid - Hessain, Hayder A; Hassan, J. J. (Iraqi Journal of Science, 2020)
A green and low-cost method was used to prepare graphene oxide (GO) and reduced graphene oxide (rGO) by chemical exfoliation of graphite powder by modified Hummers method, followed by reduction using ascorbic acid. X-ray diffractometry (XRD) and field emission scanning electron microscopy (FE-SEM) were used to analyze the structure and morphology of the synthesized materials. Fourier transform infrared spectroscopy (FTIR) and ultraviolet-visible spectroscopy were used to identify the formation of the GO and rGO